Older adult visits to the emergency department for ambulatory care sensitive conditions. Issue 5 (30th June 2020) - Lesser, Adriane; Israni, Juhi; Lo, Alexander X.; Ko, Kelly J.
Abstract: Objectives: Ambulatory‐care‐sensitive conditions (ACSCs) represent emergency department (ED) visits and hospital admissions that might have been avoided through earlier primary care intervention. We characterize the current frequency and cost of ACSCs among older adults (≥65 years of age) in the ED. Methods: This study is a retrospective analysis of Centers for Medicare and Medicaid Services (CMS) national claims data distributed by the Research Data Assistance Center, a CMS contractor based at the University of Minnesota. We analyzed outpatient ED‐based national claims data for visits made by traditional fee‐for‐service (FFS) Medicare beneficiaries in 2016. ACSCs were identified according to the Agency for Healthcare Research and Quality's Prevention Quality Indicators criteria, which require that the ACSC be the primary diagnosis for the visit. Analysis was done in Alteryx and R. Results: We documented nearly 1.8 million ACSC ED visits in 2016, finding that ≈10.6% of all ED visits by older adult FFS Medicare beneficiaries were associated with an ACSC. ACSC ED visits resulted in admission more often (39.7%) than non‐ACSC ED visits (23.9%). Notably, 83% of patients with short‐term complications from diabetes were admitted. Conclusions: ED visits for a primary diagnosis of an ACSC highlight opportunities to improve access to preventive care, particularly earlier recognition and treatment of patients' deteriorating conditions that could have potentially precluded the need for the ED visit. An opportunity exists to leverage ED‐based initiatives during an ACSC ED visit to support appropriate community and care transitions of these high‐risk patients.